More flexibility for more innovation? Evidence from the Netherlands - Wachsen, Eva; Blind, Knut (Amsterdam, 2011)
"Labor market flexibility continues to be one of economics, politics and society highly debated topic. In recent years, the impact of increased labor market flexibility on research and innovation has gained more and more attention. Previous studies have shown, depending on the measurement of flexibility as well as on the data that both positive and negative influences can be found. However, the financial flexibility in terms of wage rigidities has hardly been explored empirically. With the use of a unique dataset combining comprehensive information from both employers and employees we can accomplish variables not only to numerical and functional, but also to financial wage flexibility. In a panel probit model, we show that the influences of most of the indicators of wage flexibility are positive and vary by type of innovation. While the variables of wage bargaining has a higher impact on process innovations, information about specific wage levels, however, affects in particular the development of new products. The same applies to a separate consideration of wage bargaining levels. Aspects of numerical and functional labor market flexibility, in contrast, act negative on all types of innovation. Thereby, part time employees affect particularly processes, while flexible employment contracts have a stronger influence on product innovations. It seems that new products depend more on employment status and the resulting motivation of the employees."